Volume 5B: Heat Transfer 2018
DOI: 10.1115/gt2018-76564
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Investigation of Optimized Blade Tip Shapes: Part I — Turbine Rainbow Rotor Testing and CFD Methods

Abstract: Blade tip design and tip leakage flows are crucial aspects for the development of modern aero-engines. The inevitable clearance between stationary and rotating parts in turbine stages generates high-enthalpy unsteady leakage flows that strongly reduce the engine efficiency and can cause thermally induced blade failures. An improved understanding of the tip flow physics is essential to refine the current design strategies and achieve increased turbine aerothermal performance. However, while past studies have ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 50 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…Maesschalck [24][25][26] apllied the carved and squealer-like tip to promote the aerodynamic thermal performance and proposed the optimization strategy. Cernat 27,28 researched the aerothermal performance of a multi-cavity squealer-like tip and a contoured shape tip by the detailed experimental and the numerical studies. The result indicated that the two tip structures had the greater impact on the static pressure coefficient (C p ) after 50%C ax .…”
Section: Introductionmentioning
confidence: 99%
“…Maesschalck [24][25][26] apllied the carved and squealer-like tip to promote the aerodynamic thermal performance and proposed the optimization strategy. Cernat 27,28 researched the aerothermal performance of a multi-cavity squealer-like tip and a contoured shape tip by the detailed experimental and the numerical studies. The result indicated that the two tip structures had the greater impact on the static pressure coefficient (C p ) after 50%C ax .…”
Section: Introductionmentioning
confidence: 99%